IMPLEMENTASI HUKUM LARANGAN MEMBERI UANG ATAU BARANG KEPADA GELANDANGAN DAN PENGEMIS DI KOTA MAKASSAR - Nurdin, Elmiati; Heryani, Wiwie; Famaur, Andi Tendri (UNES Law Review, 2023)
The prohibition of giving money or goods to homeless people and beggars in Makassar City is regulated in Article 49 of Regional Regulation Number 2 of 2008 concerning the Development of Street Children, Homeless People, Beggars and Singers. This ban was issued to prevent the development and spread the number of homeless and beggars and minimize or free public places from the presence of homeless people and beggars. This study aims to analyze the implementation and application of sanctions for giving money or goods to homeless people and beggars. The results of the study show that the implementation of the rules regarding the prohibition giving money or goods to homeless people and beggars in Makassar City has not gone well. The indicators are that there are still policy objectives that have not been achieved, the number of officers is not proportional to number (riders) and the size of the area, the unavailability of adequate facilities/facilities, and the low level of public legal awareness. The lack of coordination between related agencies and the absence a government account to collect money from fines resulted in the implementation/enforcement of sanctions for giving money or goods to homeless people and beggars in Makassar City.